Binding of pyrazine-functionalized calix[4]arene ligands with lanthanides in an ionic liquid: thermodynamics and coordination modes. Issue 14 (6th March 2015) - Ansari, Seraj A.; Mohapatra, Prasanta K.; Verboom, Willem; Zhang, Zhicheng; Dau, Phuong D.; Gibson, John K.; Rao, Linfeng
Abstract : Complexation thermodynamics of Eu 3+ with pyrazine-functionalized calix[4]arene in ionic liquid was investigated by absorption spectroscopy, luminescence spectroscopy and microcalorimetry. Abstract : The complexation of representative lanthanides with three calix[4]arenes functionalized with four pyrazine pendent arms containing different substituents such as carbamoyl dioctyl (LI ), diisopropyl phosphonate (LII ), and diphenyl phosphoryl (LIII ) was investigated in water-saturated 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BumimTf2 N) by absorption spectroscopy, luminescence spectroscopy, and microcalorimetry. All three ligands form 1 : 1 ML complexes (M = Eu 3+ and L = ligand), and the stability constants (log  β ) follow the order:LI (−1.38 ± 0.66) ≪LII (3.71 ± 0.02) <LIII (7.47 ± 0.03), similar to the trend in the metal distribution coefficients in solvent extraction using these ligands as extractants. The enthalpy of complexation, determined by microcalorimetry, shows that the complexation of lanthanides with these bulky ligands is exothermic, and proceeds via replacement of water molecules from the primary coordination spheres. The 1 : 1 stoichiometry of the ML complexes was confirmed by electrospray ionization mass spectrometry. Results from optical absorption, luminescence and 31 P-NMR spectroscopy suggest that, out of four pendent arms on the rigid calixarene platform, only two arms coordinate with the lanthanide ion and each arm is tridentate. The influence of structural features of the ligand on the complexation of lanthanides is explained with the help of thermodynamic parameters.